2014 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--22870
|View full text |Cite
|
Sign up to set email alerts
|

Non-Curricular Activities Help African-American Students and Alumni Develop Engineer of 2020 Traits: A Quantitative Look

Abstract: She holds a B.S., M.S., and Ph.D. in civil engineering and a graduate certificate in engineering education-all from Clemson University. Until 2012, she was the director of the Savannah River Environmental Sciences Field Station. Dr. Simmons has nearly fourteen years of engineering and project management experience working with public utility companies, a project management consulting company, and a software company. She is a registered professional engineer, project management professional and LEED accredited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Engineering education scholars have documented the experiences of Black and African American engineering students and explored the influence of precollege extracurricular engagement on their engineering knowledge and identity (J. P. Martin et al, 2015; Simmons & Martin, 2011; Simmons et al, 2014; Young et al, 2014). A majority of the research on the influence of family members on Black males' success in engineering has centered on postsecondary students' reflections on their precollege experiences.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Engineering education scholars have documented the experiences of Black and African American engineering students and explored the influence of precollege extracurricular engagement on their engineering knowledge and identity (J. P. Martin et al, 2015; Simmons & Martin, 2011; Simmons et al, 2014; Young et al, 2014). A majority of the research on the influence of family members on Black males' success in engineering has centered on postsecondary students' reflections on their precollege experiences.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The contribution of co-curricular and extracurricular activities to students' leadership knowledge, skills, and attitudes has been previously reported; Ostadalimakhmalbaf and Simmons [32] cited six papers from their literature review that linked student leadership development with participation in professional societies and associated design competitions. More specifically, Simmons et al [33] found that National Society of Black Engineers (NSBE) participants reported that participation in the organization was highly influential to developing their leadership traits (mean 3.99 on a scale of 1 to 5); this was the strongest among ten traits and also higher than students reported for participation in minority engineering programs (mean 3.52), while leadership development was similar in fraternities/sororities (mean 3.81).…”
Section: One Student Described Their Leadership Experiences Via Ewb As Followsmentioning
confidence: 99%
“…Initially, African American engineering alumni from U.S. institutions were recruited because of their ability to reflect on how their collegiate experiences have influenced their careers over time [35]. Participants were recruited through the organizations of interest.…”
Section: B Participant Selectionmentioning
confidence: 99%